A comparison of radioactive thallium and potassium fluxes in the giant axon of the squid. - Landowne, D (1975)
1. The influx and the efflux of 204Tl and 42K were measured in intact squid giant axons. 2. The resting efflux of 204Tl was found to be about one half of 42K and to have a temperature coefficient (Q10) of 1-3 as compared to 1-1 for K. 3. The extra efflux of 204Tl associated with nerve impulses was 30% greater than 42K. 4. From either Cl or NO3 sea water, the resting influx of 204Tl was about three times that of 42K. Ouabain reduced the influx of either isotope by about two thirds without changing the Tl/K ratio of the fluxes. This indicates that the Na pump can transport Tl. 5. From NO3 sea water the extra influx of 204Tl assoicated with nerve impulses was about the same as 42K. From Cl sea water there was no detectable extra influx of 204Tl. 6. The flux ratio, ouabain-insensitive influx/efflux, was different for the two ions. The resting flux ratio for Tl was consistent with a passive non-interacting flux, whereas K movements were consistent with 'single file' passage through the membrane. 7. The extra flux associated with nerve impulses is different from the resting flux both in Tl/K selectivity and in the effect of anion in the sea water. There is also a much higher flux per unit time during the nerve impulse. These differences suggest differences in the mechanisms underlying ion permeability at rest and during nervous activity.